2023
DOI: 10.1021/acsanm.2c05307
|View full text |Cite
|
Sign up to set email alerts
|

Nonmodified Laser-Induced Graphene Sensors for Lead-Ion Detection

Abstract: Electrochemical detection, especially anodic stripping voltammetry (ASV), has been widely used in the detection of heavy metal ions because of its high sensitivity, low detection limit, as well as on-site and real-time detection capability. However, ASV detection typically relies on modified sensors, which complicates the preparation process and introduces contaminants to the tested solutions. Herein, we developed a preconcentration relaxation strategy to improve detection performances of bare sensors without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…High‐resolution transmission electron microscopy (HRTEM) images of the all the X%‐Ce─ZnO samples displayed distinct lattice spacings of 0.248 and 0.311 nm (Figure 2c; Figure S2, Supporting Information), corresponding to the ZnO(101) and the CeO 2 (111) planes, respectively. [ 22,23 ] For comparison, the single metal oxide CeO 2 or ZnO catalysts retained the morphologies and sizes of their respective components in the composite catalysts (Figure S3, Supporting Information). For the 10%‐Ce─ZnO sample, abundant defects were observed on the edges of those two oxides (Figure 2c; Figure S4, Supporting Information), suggesting the existence of rich Ce─O─Zn structures.…”
Section: Resultsmentioning
confidence: 99%
“…High‐resolution transmission electron microscopy (HRTEM) images of the all the X%‐Ce─ZnO samples displayed distinct lattice spacings of 0.248 and 0.311 nm (Figure 2c; Figure S2, Supporting Information), corresponding to the ZnO(101) and the CeO 2 (111) planes, respectively. [ 22,23 ] For comparison, the single metal oxide CeO 2 or ZnO catalysts retained the morphologies and sizes of their respective components in the composite catalysts (Figure S3, Supporting Information). For the 10%‐Ce─ZnO sample, abundant defects were observed on the edges of those two oxides (Figure 2c; Figure S4, Supporting Information), suggesting the existence of rich Ce─O─Zn structures.…”
Section: Resultsmentioning
confidence: 99%
“…[ 67 ] In the Co 2p XPS spectra, the ratio of Co 3+ /Co 2+ (≈3.8) after the OER test is higher than that of pristine catalyst (≈1.19) (Figure S23, Supporting Information), indicating that partial Co 2+ is oxidized into Co 3+ to form the CoOOH on the c‐CoSe 2 ‐CoN/NC during the OER process. [ 68 ] Furthermore, a slight change in the ratio of Co 3+ /Co 2+ (≈1.6) is observed after the ORR stability test, further indicating that c‐CoSe 2 ‐CoN/NC possesses good structural stability. To understand the reaction mechanisms more intuitively, Figure 6h illustrates the origins of electrocatalytic activity and the fate of active ingredients in c‐CoSe 2 ‐CoN/NC after ORR/OER.…”
Section: Resultsmentioning
confidence: 96%
“…[39,40] The conductivity is another factor determining the detection performance of electrochemical sensors, i.e., higher conductivity is associated with higher detection performance. [31,32] In order to improve the conductivity of LIG, we changed laser power and laser speed and took the sheet resistance as the indicator. It was found that as the laser power increases from 9.2 to 9.6 W, the sheet resistance of LIG decreases first and then increases (Figure 2e).…”
Section: Preparation Of Ligmentioning
confidence: 99%
“…As shown in Figure 2f, the charge transfer resistance (R ct ) of LIG can be read as 3.5 Ω from the diameter of the minicircle, indicating the low electrochemical impedance and strong charge transfer ability of LIG. [32,43]…”
Section: Preparation Of Ligmentioning
confidence: 99%